Characterization of Biochars Produced by Co-Pyrolysis of Hami Melon (Cantaloupes) Straw Mixed with Polypropylene and Their Adsorption Properties of Cadmium - Changheng Li (MDPI AG, 2021)
Reuse of waste from Hami melon (cantaloupes) straws (HS) mingled with polypropylene (PP) ropes is necessary and beneficial to mitigate environmental pollution. The objective of this study was to investigate the characteristics and mechanisms of Cd2+ adsorption on biochars produced by co-pyrolysis of HS-PP with various mixing ratios. N2-sorption, scanning electron microscopy (SEM), energy dispersive X-ray spectrometer (EDS), elemental analysis, Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), thermal gravity, and differential thermal gravity (TG/DTG) were applied to evaluate the physicochemical properties of materials. Batch adsorption experiments were carried out for investigating the effects of initial pH, Cd2+ concentration, and adsorption time. It was found that the Langmuir and pseudo-second-order models fitted best for the experimental data, indicating the dominant adsorption of co-pyrolysis biochars is via monolayer adsorption. Biochar derived at 4/1 mixing ratio of HS/PP by weight percentage had the highest adsorption capacity of 108.91 mg·g−1. Based on adsorption isotherm and kinetic analysis in combined with EDS, FTIR, and XRD analysis, it was concluded that the main adsorption mechanism of co-pyrolysis biochar involved the surface adsorption, cation exchange, complexation of Cd2+ with surface functional groups, and chemical precipitation. This study also demonstrates that agricultural wastes to biochar is a sustainable way to circular economy.